Một số khảo sát thực tế về sự hình thành các hệ đếm 5, hệ đếm 10 và hệ đếm 20 /Hoàng Thị Châu. - Hoàng, Thị Châu.
The retrospective method enables us to visualize some of our primitive numeration in the past through sesidue words such as “hand”, “finger” in the present numeral systems. The mirror reflecting our ancient societies is the present day of communities, who live by gathering and hunting as the Papaua-New Guineans in the Pacific Ocean, the Eskimo-Aleutians on the coast of the Arctic Ocean. The investigation of the numeral system of some communities in these 2 regions shows that although they are living far from each other, with different nature and climates they have similarities in the formulation of quinary, decimal, vigesimal numerations with words like hand and human body, an evidence of the universality in formation of thought and language.